Effect of management factors on reproductive and milk production performance of a dairy sheep breed adapted to low-input management systems - TZANIDAKIS, N.; VOUTZOURAKIS, N.; STEFANAKIS, A.; BROZOS, C. N.; SOTIRAKI, S.; KIOSSIS, E. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Interest on the implementation and improvisation of low-input dairy sheep farming is rising. Our study aimed to describe a) the milk productivity of the Sfakia sheep, a Mediterranean well-adapted to low-input management schemes breed (“low-input breed”), and b) the effect of management (MS) and milking system (MLS) on milk yield and quality. Monthly bulk milk samples (n=307) and reproductive data were collected from 10 extensive and 10 semi-intensive Sfakia sheep flocks in Crete Greece, over two consecutive lactations. All semi-intensive and four extensive farms were equipped with a milking parlour machine (MPM). A portable machine (PM) was used in three extensive farms; hand-milking (HM) was applied in the rest extensive farms. The effect of MS and MLS on daily milk yield/ewe (DMY), somatic cell count (SCC), total bacterial count (TBC), pH and % lactose content (LACT) of milk was explored with linear mixed-effects models. Mean DMY (p<0.001) as well as the seasonal variation pattern of SCC (p=0.020) and LACT (p=0.018) differed between MS. TBC was higher in extensive farms using MPM than HM (p=0.002); PM was related to lower SCC, compared to MPM (p=0.044) and HM (p=0.012). Concluding, mild interventions in management and milking practices could improve the productivity of “low-input” dairy sheep breeds.